DISCOURSE ANALYSIS AND PRAGMATICS - Madjidova, Diyora (Журнал иностранных языков и лингвистики, 2021)
In this article an important assumption of discourse analysis is given as a tool that shapes people's perceptions of the world. Further developments in speech-act theory contend that language also actively constructs social reality.